The Religions of India : A Microcosm of World Religions - Kassam, Meenaz, (Brill | Manohar Publishers & Distributors, 2019)
This volume is about the religions of India as well as about world religions given that India is the repository of the world's greatest religions: Hinduism, Islam, Christianity, Buddhism, Jainism, Sikhism, Zoroastrianism and Judaism. A distinctive feature of this volume is that a scholar who is a specialist in a particular religion describes each of the great religions. Every chapter is an academic study of a particular religion that not only explains the religion but also connects its history to its unique development in India by showing how it got there. Four great religions originated in India: Hinduism, Buddhism, Jainism and Sikhism. These have been well elucidated in the relevant chapters and their development assessed for causal and dynamic influences. The socio-historical framework illustrates how, though only four of the Indian religions have originated in India, the other religions like Islam, Christianity, Zoroastrianism and Judaism, have, over time, been Indianized or taken on Indian cultural characteristics. The volume, an introductory text, is a timely and unique collaboration introducing readers to world religions while simultaneously building an overall picture of how these religions became, over time, 'The Religions of India'.